Bronchopulmonary sequestration as a cause of mismatched perfusion defect on single-photon emission computed tomography ventilation-perfusion scan - Michael Kreltszheim; Nick Brown; Joseph Lee (World Journal of Nuclear Medicine)
We present a 46-year-old female with pleuritic chest pain on a background of pulmonary embolism diagnosed on a single-photon emission computed tomography (SPECT) ventilation-perfusion (V/Q) imaging 3 years earlier. A SPECT V/Q scan detected a mismatched perfusion defect in the posterior basal segment of the right lower lobe, essentially unchanged from a defect identified 3 years earlier. Given the atypical finding, the patient went on to have a computed tomographic pulmonary angiogram. It revealed an intralobar bronchopulmonary sequestration as the cause of the right lower lobe mismatched perfusion defect. With growing awareness of radiation safety, the number of V/Q imaging studies being undertaken to investigate suspected pulmonary emboli, especially in young female patients, has increased. This case report serves as a timely reminder of the potential pitfalls associated with V/Q scan image interpretation.